ORIENTASI PASAR, MODERASI DINAMIKA LINGKUNGAN PADA EFEK STRATEGI BERSAING TERHADAP KINERJA (Studi Pada Industri Kecil Menengah Tenun di Sulawesi Tenggara) - ROSNAWINTANG ; Prof. Dr. Ubud Salim, SE., M.A,Prof. Armanu, SE., M.Sc., Ph.D ,Dr. Mintarti Rahayu, SE., M.Si
The study aims to measure and analyze the influence of market orientation on _x000D_ competitive strategy and performance, that competitive strategy on performance and_x000D_ the moderation of environment dynamics of competitive strategy on performance at the_x000D_ weaving small and middle scale industries (SMIs) in Southeast Sulawesi. _x000D_ The object of the study is the weaving SMIs in Southeast Sulawesi. The data_x000D_ are primary data and the population is 219 units of weaving SMIs. The sampling_x000D_ technique is Saturated Sampling. The number of returned questionnaires is 202 units_x000D_ and among them 2 units cannot be analyzed and thus, the population that could be_x000D_ analyzed is 200 units of weaving SMIs spreading at the 5 (five) regencies/municipalities_x000D_ in Southeast Sulawesi. The analysis instrument is SEM (Structural Equation Model)_x000D_ with Amos Program 16. _x000D_ The findings of the study show that increasing performance of the SMIs in_x000D_ Southeast Sulawesi is done directly through market orientation effectiveness and_x000D_ indirectly done through proper competitive strategy application. The environment_x000D_ dynamics strengthens the appropriateness of competitive strategy to increase the_x000D_ performance of the weaving SMIs in Southeast Sulawesi. The market effectiveness of_x000D_ market orientation done through customers’ orientation with competitive strategy_x000D_ through product differentiation has increased the performance of the weaving SMIs._x000D_ The appropriate application of competitive strategy suitable with environment dynamic_x000D_ through the intensity of competition encourages the increase of performance at the _x000D_ market share extension of the weaving SMIs in Southeast Sulawesi. _x000D_ _x000D_ Key Words: Market Orientation, Environment Dynamics, Competitive Strategy,_x000D_ Performance.